Think Before You Post: Cerdas Berkomunikasi Di Era Digital - Arief A.S; Fahmi Alhadi; Nawaf Alhadi; Sofia Nugraheni; Sela Denita; Nova Fitri; Ocha Shelvia; Juraida; Widia Rahmasia; Afnizah; Iwan Doa Sempena (PT. Hasba Edukasi Mandiri, 2026)
In the digital era, social media has become a communication tool used by various segments of society. The ease of disseminating information requires internet users to be more prudent in using social media. This journal discusses the importance of the